Ecologism towards ecological citizenship - Smith, Mark J. 1962- (Open Univ. Press, 1998)
Smith outlines the distinctive features of ecological thought and examines two contentious areas of environmental ethics, the obligations for present generations and the relationship of humans to non-human animals.
Keywords: Ecologie humaine - Philosophie; Ecologisme; Ethique de l'environnement; Milieuethiek; Écologie humaine - Philosophie; Écologisme; Éthique de l'environnement; Philosophie; Environmental ethics; Green movement; Human ecology -- Philosophy; Umweltschutz; Umweltbewusstsein; Sozialordnung; Umweltethik; Politik